ANALISIS PENGARUH BUDAYA ORGANISASI, KOMPETENSI, DAN BEBAN KERJA TERHADAP KINERJA APARATUR SIPIL NEGARA (ASN) PADA KOPERTIS WILAYAH XII DI KOTA AMBON - Stevy Moniharapon (Manis: Jurnal Manajemen dan Bisnis, 2019)
This study aims to determine the effect of organizational culture, competence, and workload on employee performance either partially or simultaneously. The population in this study were ASN employees at the Region XII Private College Coordination Office in Ambon City, amounting to 39 people. The number of samples used in this study 39 staff obtained by using the sampling technique used is the census method. Data collection techniques used were questionnaires and interviews. Data analysis method uses descriptive statistical and multiple regression analysis with using SPSS for Windows version 22. The results showed that there was a positive and significant direct influence of organizational culture on performance with a significance value of 0.002 <0.05 and t arithmetic (3.362)> from t table (2.03), there was a positive and significant direct influence of competence on performance with significance value 0.007 <0.05 and t count (2.858)> from t table (2.03), there is a positive and significant direct effect on the workload on performance with a significance value of 0.041 <0.05 and t count (2.127)> from t table ( 2.03), there is a positive and significant direct influence on organizational culture, competence, and workload on performance with a significance value of 0.000 <0.05 and F arithmetic (27.666)> from F table (2.87).